Shining bright in the dusk: How do bat-pollinated flowers reflect light? - Domingos Melo, Arthur (2021)
Specialization in nectarivory is an uncommon condition among bats, and it is restricted to two subfamilies of neotropical phyllostomids (Glossophaginae and Lonchophyllinae) which encompass dozens of bats with striking morpho-physiological adaptations to exploit floral nectar (Muchhala and Tschapka 2020). Such bats commonly start the search for flowers before the sun goes down, when the flowers are freshly opened (Sazima and Sazima 1975). After spotting a resource, nectarivorous bats prefer to use spatial memory instead of floral clues to look for new flowers (Carter et al. 2010). Therefore, it may be essential that chiropterophilous (i.e. bat-pollinated) flowers are attractive to bats during the early part of their searching routine when they build in their minds a trace of their foraging bouts. It is known that bats find flowers by integrating acoustic and olfactory cues, which are very useful in dark conditions (Gonzalez-Terrazas et al. 2016). However, since there still is plenty of light striking flowers during twilight, the question emerges: Do these flowers reflect light that also draws the attention of bats by addressing their color vision abilities?